On the Expected Discounted Penalty Function for the Classical Risk Model with Potentially Delayed Claims and Random Incomes - Huiming Zhu; Ya Huang; Xiangqun Yang; Jieming Zhou (Journal of Applied Mathematics)
We focus on the expected discounted penalty function of a compound Poisson risk model with random incomes and potentially delayed claims. It is assumed that each main claim will produce a byclaim with a certain probability and the occurrence of the byclaim may be delayed depending on associated main claim amount. In addition, the premium number process is assumed as a Poisson process. We derive the integral equation satisfied by the expected discounted penalty function. Given that the premium size is exponentially distributed, the explicit expression for the Laplace transform of the expected discounted penalty function is derived. Finally, for the exponential claim sizes, we present the explicit formula for the expected discounted penalty function.